Travail et citoyenneté : quel avenir ? - Legault, Marie-Josée (Relations industrielles / Industrial Relations, 2011)
The article reviews the book, "Travail et citoyenneté : quel avenir ?," edited by Michel Coutu and Gregor Murray.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z